Green Building Implementation Model in Tasikmalaya City Public Service Mall: An Environment-Based Approach - Rusli, Budiman; Muharam, Riki Satia (Journal of Ecohumanism, 2025)
The Green Building implementation model in the Tasikmalaya City Public Service Mall (MPP) with an environment-based approach aims to create efficient, sustainable, and environmentally friendly public facilities. This study develops a model that integrates sustainability principles in the design, operation, and management of MPP, taking into account the local characteristics of Tasikmalaya City. The main focus of this model includes energy efficiency through energy-saving technology and renewable energy sources, efficient water management, and the use of environmentally friendly building materials available around the region. The implementation of Green Building in MPP is expected to reduce operational costs, increase user comfort and satisfaction, and reduce environmental impacts, such as reducing carbon emissions and conserving natural resources. This model also encourages the importance of collaboration between the government, the private sector, and the community in its implementation. By providing policy recommendations and strategies for the implementation of Green Building in other public facilities, this research aims to make Tasikmalaya City a model environmentally friendly city in Indonesia.